2014
DOI: 10.1074/jbc.m114.583989
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Length Peptide-Pheromone Variants Produced by Streptococcus pyogenes Directly Bind Rgg Proteins to Confer Transcriptional Regulation

Abstract: Significance: Bioactivity and receptor-ligand affinity assays developed herein provide a platform to discover quorum-sensing inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 32 publications
1
66
0
1
Order By: Relevance
“…As shown in Fig 9B, S . suis has a high affinity for its cognate XIP-C7 with a K d similar to that observed for SHPs and Rggs (Table 2) [39]. Additionally, the binding mechanism is driven by hydrogen bonding and likely electrostatic interactions as indicated by the large enthalpy, which again emphasizes the importance of the electropositive pocket (Fig 5C).…”
Section: Resultssupporting
confidence: 62%
“…As shown in Fig 9B, S . suis has a high affinity for its cognate XIP-C7 with a K d similar to that observed for SHPs and Rggs (Table 2) [39]. Additionally, the binding mechanism is driven by hydrogen bonding and likely electrostatic interactions as indicated by the large enthalpy, which again emphasizes the importance of the electropositive pocket (Fig 5C).…”
Section: Resultssupporting
confidence: 62%
“…To identify inhibitors of Rgg function, we developed a fluorescence polarization (FP) assay whereby drug and druglike compounds (Prestwick Chemical) were screened for their ability to disrupt the binding of fluorescent-labeled synthetic SHP peptides (FITC-SHP) to Rgg Sp (26) or Rgg2 Sd (Fig. 3 C-D).…”
Section: Resultsmentioning
confidence: 99%
“…1B) with similar affinities, and Rgg2 Sp and Rgg3 Sp bind to identical DNA-regulatory elements upstream of their target promoters (21,26). The net response of S. pyogenes to SHP pheromone is the robust expression of Rgg2/3-controlled promoters; however, Rgg2 Sp and Rgg3 Sp affect transcription by different mechanisms.…”
mentioning
confidence: 99%
“…Our lab has previously shown that shp3 has greater potential to activate Rgg-SHP signaling than shp2 ; using a series of gene replacements and by constructing chimeric shp s, it was determined that the difference in activation potential lies in the non-effector N-terminal portion of the peptides [23]. Furthermore, mature pheromones (C-terminal eight amino acids; Table 1) bind the Rgg proteins and induce P shp signaling with similar EC 50 values [13,23]. However, we have also shown that an aminopeptidase, PepO, degrades SHPs and limits signaling, with SHP2-C8 inactivated more efficiently than SHP3-C8 [19].…”
Section: Resultsmentioning
confidence: 99%
“…pyogenes [5], but is not required to produce XIP in S . mutans [12], and additional processing steps may occur in the final maturation of either peptide [13]. However, the mechanism by which XIP and SHP peptides are exported from the cell remains poorly understood for the model systems of S .…”
Section: Introductionmentioning
confidence: 99%